A biomechanical view on stinger diversity in scorpions. Issue 4 (28th December 2016) - van der Meijden, Arie; Kleinteich, Thomas
Abstract: Scorpions have elongated metasomas that bear a telson, which is used as a stinger for venom injection. There is a remarkable diversity in the use of the stinger among scorpions, comprising defensive behavior, prey subjugation and mating. This diversity could be reflected by the shape of the telson, as different stinging behaviors will result in very different functional demands. Here we explored the diversity of telson shapes in scorpions by providing morphological measurements, such as curvature and tip angle, as well as by testing stingers under load using finite element analysis (FEA). FEA models were loaded with forces scaled to the surface area of the models, to allow comparison of the relative strain energy based on shape alone. Load force angle was rotated to identify the optimal stinging angle based on the lowest strain energy. Aculeus length and mean aculeus height correlated with minimal strain energy. Optimal stinging angle correlated with tip angle, and differed from the tip angle by about 28.4 ± 6.22 °. We found that species that are more venomous have long aculei (stinger barbs) with a larger radius of curvature. FEA models of these longer aculei showed basal stress concentrations, indicating a potential greater risk of basal breakage due to shape alone. Telsons with shorter and thicker aculeus shapes showed stress concentrations at the tip only. Despite these marked differences in shape, we found no difference in the scaled strain energy between groups of species that are more venomous and less venomous groups of species. These results show that scorpion stingers may be biomechanically optimized, and this may indicate different usage of the stinger in different species.